Artificial noise aided directional modulation via reconfigurable intelligent surface: Secrecy guarantee in range domain. Issue 13 (17th May 2022) - Chen, Jiangong; Xiao, Yue; Lei, Xia; Niu, Hong; Yuan, Yanli
Abstract: Recently, the physical limitation of range‐domain security guarantee for directional modulation with frequency diverse array was disclosed in Ding et al. ( IEEE Access 8, 63302–63309 (2020)). Therefore, to recreate this significant secrecy realisation in both direction and range domain, the authors conceive an artificial noise aided directional modulation scheme via reconfigurable intelligent surface. Specifically, the angle of departure from the reconfigurable intelligent surface to co‐direction receivers varies with distance, which provides the freedom to distinguish users in the range domain. With locations of the active eavesdroppers, an optimisation problem is further formulated to maximise the secrecy rate, which is then solved by applying genetic algorithm and alternating optimisation. On the other hand, when the eavesdroppers are silent, we employ maximum‐ratio transmission precoding and artificial noise to guarantee information security. Finally, simulation results demonstrate that, due to the aid of reconfigurable intelligent surface, the developed directional modulation structure can robustly guarantee the information security in the range domain, whether the information of eavesdroppers is achieved.